2014
DOI: 10.5424/sjar/2014121-3803
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting somatic cell count in dairy goats: a review

Abstract: Somatic cell count (SCC) in monitoring udder health has been described in numerous studies as a useful method for the diagnosis of intramammary infection (IMI), and it is considered in standards of quality and hygiene of cow's milk in many countries. However, several authors have questioned the validity of SCC as a reliable IMI diagnosis tool in dairy goats. This review attempts to reflect the importance of different infectious and non-infectious factors that can modify SCC values in goat milk, and must, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
2
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 77 publications
3
71
2
8
Order By: Relevance
“…In dairy animals, SCC is an important milk characteristic possibly related to animal welfare. Research in dairy goats suggests that this indicator is related to intramammary infections, as SCC increases in presence of clinical or subclinical mastitis Koop et al, 2012), although the latter is asymptomatic and is not reported to affect goat welfare (Jimenez-Granado et al, 2014). Somatic cell count is routinely collected herd data on bulk milk; therefore, it is available in most farms.…”
Section: Absence Of Diseasementioning
confidence: 99%
“…In dairy animals, SCC is an important milk characteristic possibly related to animal welfare. Research in dairy goats suggests that this indicator is related to intramammary infections, as SCC increases in presence of clinical or subclinical mastitis Koop et al, 2012), although the latter is asymptomatic and is not reported to affect goat welfare (Jimenez-Granado et al, 2014). Somatic cell count is routinely collected herd data on bulk milk; therefore, it is available in most farms.…”
Section: Absence Of Diseasementioning
confidence: 99%
“…Milk SCC in goats is commonly higher than in cattle and sheep (Contreras et al, 2007). Furthermore, the ability of milk SCC to predict IMI may be lower in goats than in cattle and sheep, as many environmental factors can increase SCC in the uninfected halves (Poutrel and Lerondelle, 1983;Boettcher et al, 2005;Contreras et al, 2007;Jiménez-Granado et al, 2014). This has raised the question of whether milk SCC is an efficient selection criterion for reducing IMI.…”
Section: Introductionmentioning
confidence: 99%
“…Somatic cell count is also included in the parameters considered for the determination of milk price in several European countries [27]. Mastitis is one of the major diseases which leads to signifi cant economic losses mainly due to discarded milk, decreased milk production, quality, early culling, and increased health care costs in dairy ewes [28][29][30][31][32][33][34][35][36][37], cows [38][39][40][41][42] and goats [43][44][45][46][47]. Studies on the genetic resistance to mastitis have increased recently, showing the economic importance of this trait [48].…”
Section: Introductionmentioning
confidence: 99%